2008
DOI: 10.1007/s00468-008-0224-9
|View full text |Cite
|
Sign up to set email alerts
|

Annual growth rings in the mangrove Laguncularia racemosa (Combretaceae)

Abstract: Stem discs from trees of known age were used to determine the periodic nature of the growth rings formed in Laguncularia racemosa and to describe the anatomical features of these rings. The growth rings were scarcely distinct on microscopic examination, but they were well distinguishable macroscopically, with alternating light brown and dark brown layers. Cross-dating analysis revealed the occurrence of annual growth rings in L. racemosa. The existence of annual growth rings in L. racemosa suggests that it may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
1
20
0
2
Order By: Relevance
“…According to the Köppen classifi cation, the regional climate can be divided into Aw (tropical hot and wet with a dry season during the winter), which is typical of the lowlands, and Af (tropical hot and wet with no dry season), which is characteristic of the adjacent slopes. According to Estrada et al (2008), the average annual temperature is 23.5 °C, and the average annual precipitation is 1,067 mm, with a weak tendency to wetter summers and drier winters. The same authors describe a high interannual variability in the precipitation pattern, with summer and winter alternating as the wetter period in the last 30 years.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Köppen classifi cation, the regional climate can be divided into Aw (tropical hot and wet with a dry season during the winter), which is typical of the lowlands, and Af (tropical hot and wet with no dry season), which is characteristic of the adjacent slopes. According to Estrada et al (2008), the average annual temperature is 23.5 °C, and the average annual precipitation is 1,067 mm, with a weak tendency to wetter summers and drier winters. The same authors describe a high interannual variability in the precipitation pattern, with summer and winter alternating as the wetter period in the last 30 years.…”
Section: Study Areamentioning
confidence: 99%
“…ESTRADA, MÁRIO L.G. SOARES and CÁTIA H. CALLADO mangrove species: Rhizophora mangle (Menezes et al 2003), R. mucronata (Verheyden et al 2004), R. apiculata (Yu et al 2004), Sonneratia apetala and Heritiera fomes (Chowdhury et al 2008), Laguncularia racemosa (Estrada et al 2008) and Luminitzera racemosa (Robert et al 2011). In most of these studies, the formation of annual rings is related to some degree of climate seasonality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Laguncularia racemosa from Rio de Janeiro, Brazil, also present distinguishable growth rings macroscopically, with alternating early wood formed between spring and autumn and consists of layers with abundant paratracheal axial parenchyma, while late wood is formed in winter and consists of narrower dark layers which are basically fibrous zones with scarce paratracheal axial parenchyma. The occurrence of a dry season in winter could be the seasonal factor determining the formation of annual rings (Duque Estrada et al, 2008). These results are relevant because a factor that may be important for the future of mangrove ecosystems is any change in precipitation (Field, 1995).…”
Section: Growth Ringsmentioning
confidence: 99%
“…In Rhizophora forests growing on saline and brackish soils in the state of Para in Brazil, Menezes et al (2003) showed that trees developed annual rings (checked with the 14 C technique) but the anatomical features were better defined in saline than in brackish sites. Anatomical analyses showed also the occurrence of annual rings in L. racemosa growing in the State of Rio de Janeiro, Brazil (Estrada et al, 2008).…”
Section: Seasonal Growth Detection By Annual Ringsmentioning
confidence: 99%